PENINGKATAN KEMAMPUAN GURU DALAM MENGEFEKTIFKAN PEMBELAJARAN MELALUI PROGRAM PEMBINAAN PROFESSIONAL GURU DAN SUPERVISI KELAS DI SD NEGERI 1 SABAHLIOH - RISMAWATI RISMAWATI (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2023)
Based on the results of limited discussions with teachers at SD Negeri 1 Sabahlioh it is known that the low professionalism of teachers is possible for several reasons, including: (1) low awareness of teachers to update their knowledge even though they have been appointed teachers for a long time, (2) opportunities for teachers to attend training -professional training is very limited, both in terms of quantity and intensity, (3) teacher meetings are less active, (4) educational supervision aimed at improving the learning process tends to focus on administrative aspects, and (5) credit for functional teacher positions which is intended to spur teacher performance in practice is only a formality. Based on the background of the problems above, the formulation of the problem in this research is: How to Improve Teachers' Capabilities in Making Learning Effective through the Teacher Professional Development Program and Class Supervision at SD Negeri 1 Sabahlioh. The aims of this study were: to improve teachers' ability to make learning effective through a teacher professional development program and class supervision at SD Negeri 1 Sabahlioh. The research was conducted at SD Negeri 1 Sabahlioh, Academic Year 2022/2023 with 12 class teachers as subjects. This research is a school action research conducted for three cycles. The application of a combination of the professional approach and the author's approach to teaching supervision using formal meeting techniques and techniques using student opinions can optimally increase the commitment of Sabahlioh 1 Public Elementary School teachers in carrying out the teaching and learning process. Through descriptive analysis, the results showed that 91.67% of teachers experienced an increase in commitment (from C to B or from B to A). ABSTRAKBerdasarkan hasil diskusi terbatas dengan para guru di SD Negeri 1 Sabahlioh diketahui bahwa rendahnya wawasan profesionalisme guru dimungkinkan karena beberapa alasan antara lain: (1) rendahnya kesadaran guru untuk memperbaharui pengetahuannya meskipun telah lama diangkat menjadi guru, (2) kesempatan bagi guru untuk mengikuti pelatihan-pelatihan profesional sangat terbatas, baik dari segi jumlah maupun dari intensitasnya, (3) pertemuan-pertemuan guru sejenis kurang aktif, (4) supervisi pendidikan yang bertujuan memperbaiki proses pembelajaran cenderung menitikberatkan pada aspek administrasi, dan (5) pemberian kredit jabatan fungsional guru yang ditunjukan untuk memacu kinerja guru pada prakteknya hanya bersifat formalitas. Berdasarkan latar belakang masalah di atas, maka rumusan masalah dalam penelitian adalah: Bagaimana Peningkatan Kemampuan Guru Dalam Mengefektifkan Pembelajaran Melalui Program Pembinaan Professional Guru Dan Supervisi Kelas Di SD Negeri 1 Sabahlioh. Tujuan Penelitian ini adalah: untuk meningkatkan kemampuan guru dalam mengefektifkan pembelajaranmelalui program pembinaan professional guru dan supervisi kelas di SD Negeri 1 Sabahlioh. Penelitian dilaksanakan di SD Negeri 1 Sabahlioh, Tahun Pelajaran 2022/2023 dengan jumlah guru sebagai subjek 12 orang guru kelas. Penelitian ini merupakan penelitian tindakan sekolah yang dilaksanakan selama tiga siklus. Penerapan kombinasi pendekatan profesi dan pendekatan penulis pada supervisi pengajaran dengan menggunakan teknik pertemuan formal dan teknik menggunakan pendapat siswa dapat meningkatkan secara optimal komitmen guru-guru SD Negeri 1 Sabahlioh dalam melaksanakan proses belajar mengajar. Melalui analisis deskriptif didapat hasil sebanyak 91,67% guru mengalami peningkatan komitmen (dari nilai C ke nilai B atau dari nilai B ke nilai A).